2012
DOI: 10.1021/ja310556n
|View full text |Cite
|
Sign up to set email alerts
|

Surface Display of a Redox Enzyme and its Site-Specific Wiring to Gold Electrodes

Abstract: The generation of a current through interaction between bacteria and electrodes has been explored by various methods. We demonstrate the attachment of living bacteria through a surface displayed redox enzyme, alcohol dehydrogenase II. The unnatural amino acid para-azido-L-phenylalanine was incorporated into a specific site of the displayed enzyme, facilitating electron transfer between the enzyme and an electrode. In order to attach the bacteria carrying the surface displayed enzyme to a surface, a linker cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 29 publications
0
65
0
1
Order By: Relevance
“…Our earlier studies with the same mutants have shown much lower bioelectrocatalytic activity for mutant D314Az. 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier studies with the same mutants have shown much lower bioelectrocatalytic activity for mutant D314Az. 20 …”
Section: Resultsmentioning
confidence: 99%
“…A 5 nm chromium adhesion layer and a 20 nm gold layer were deposited using K575X sputter coater (Quorum Technologies, Kent, UK). Bacteria were attached to the surface as described in ref (20). …”
Section: Methodsmentioning
confidence: 99%
“…This allows amino acids with novel functionalities to be introduced at specific locations within proteins, and such residues can be subsequently targeted in bio‐orthogonal chemical ligations . This is a rapidly expanding field of research and there are now examples of such methodologies being adapted for covalent crosslinking of redox proteins and enzymes to electrode surfaces . A practical consideration that makes the use of UAA mutagenesis potentially unsuitable for “wiring” redox metalloenzymes onto electrodes is that highly complex biosynthetic pathways can make protein overexpression challenging; in such scenarios substantial quantities of synthetic UAA may be required to generate useable quantities of UAA containing protein.…”
Section: Crosslinking Strategies For Site‐specifically Connecting Promentioning
confidence: 99%
“…[4,9,10] These BFC-based sensors open the way for future point-of-care testinga nd might provide ah elpfuls olution to low-cost and simplea nalytical systems without the need of any additional externale nergy.T od ate, the studies on BFC-baseds ensors mainly focus on their long-term operation, miniaturization, and extendt he analytes scope. However,afew reports are focused on regulating/ort uning electrocatalytic processes at the electrode surface of BFCs, [15,16] whichi st he most fundamental factorf or the development of BFC-based biosensors.…”
Section: Introductionmentioning
confidence: 99%